2009
DOI: 10.2741/3306
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of vertebrate opioid receptors

Abstract: The proteins that mediate the analgesic and other effects of opioid drugs and endogenous opioid peptides are known as opioid receptors. Opioid receptors consist of a family of four closely-related proteins belonging to the large superfamily of G-protein coupled receptors. The three types of opioid receptors shown unequivocally to mediate analgesia in animal models are the mu (MOR), delta (DOR), and kappa (KOR) opioid receptor proteins. The role of the fourth member of the opioid receptor family, the nociceptin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 204 publications
(179 reference statements)
4
50
0
Order By: Relevance
“…Similar to mammals, zebrafish possess a functional opioidergic system, including both opioid peptides and their receptors (Gonzalez-Nunez and Rodriguez, 2009;Stevens, 2009;Sundstrom et al, 2010). Supporting the utility of zebrafish in opioid research, recent behavioral studies have confirmed their sensitivity to the rewarding properties of morphine (Bretaud et al, 2007;Lau et al, 2006).…”
Section: Opioidergic Systemmentioning
confidence: 91%
“…Similar to mammals, zebrafish possess a functional opioidergic system, including both opioid peptides and their receptors (Gonzalez-Nunez and Rodriguez, 2009;Stevens, 2009;Sundstrom et al, 2010). Supporting the utility of zebrafish in opioid research, recent behavioral studies have confirmed their sensitivity to the rewarding properties of morphine (Bretaud et al, 2007;Lau et al, 2006).…”
Section: Opioidergic Systemmentioning
confidence: 91%
“…Phylogenetic analysis suggests two rounds of genome-wide duplication (paleoploidization) from a single ancestral opioid gene (unireceptor) (Ohno, 1999;Escriva et al, 2002;Lundin et al, 2003), with the first yielding the ancestral DOR-1/MOR-1 and ORL-1/KOR-1 genes. The duplication then led to DOR-1 and MOR-1, as well as KOR-1 and ORL-1 (Dreborg et al, 2008;Larhammar et al, 2009;Stevens, 2009). The predicted MOR-1 protein sequences from 27 species reveals four major clades as follows: 1) fish, 2) amphibians, 3) birds, and 4) mammals, mimicking the evolutionary tree of life (Fig.…”
Section: B Phylogeny and Evolutionmentioning
confidence: 99%
“…Other investigators have also suggested that studies of chromosomal location may shed light on opioid receptor evolution (37). We describe here an investigation, using a combination of sequence-based phylogenies and gene locations for the opioid receptors and their neighboring families that shows that they expanded by gene duplications in conjunction with the proposed tetraploidizations in early vertebrate evolution.…”
mentioning
confidence: 99%